Pemilihan Material Yang Aman Untuk Frame Sepeda Listrik - Alviani Hesthi Permata Ningtyas; Ilham Arifin Pahlawan; Rafli Pramudia Putra (SITEKIN: Jurnal Sains, Teknologi dan Industri, 2022)
Material properties or often referred to as mechanical properties are properties of materials related to behavior towards mechanical loading. Mechanical properties are necessary in considering the selection of materials that correspond to the circumstances required at loading. In addition to mechanical properties, dimensions are also needed that have a large role in assessing the strength of a bicycle frame. In this study, a material selection analysis process will be carried out based on the stress, displacement and safety factoe on the bicycle frame. The materials used in this study were aluminum 6061, steel and carbon with variations in loading of 60kg, 75kg, and 90kg. The analysis process is carried out using Autodesk inventor software. Where from the results of the 2018 Inventor software analysis obtained the value of von misses stress, displacement and safety factors. The conclusion obtained in this study is that the highest load has a maximum voltage owned by aluminum material 6061 and the displacement is the largest owned by carbon material. Safety factor worth more than 1 is owned by all materials, namely aluminum 6061, carbon and steel so that all materials are safe to use as electric bicycle frames.